Medical Faculty Students' Academic Motivation Types: A Comparison with Respect to Various Variables - Alci, Bulent (KAMLA-RAJ ENTERPRISES, 2016)
The purpose of this paper is to determine the types of academic motivation of medical faculty students according to the type of university they study at and their gender. The study group of this descriptive paper consists of 165 students who study at a state university and 162 students who study at two private universities. The total number of the study group was 327 medical faculty students. In order to find out the motivation types of the students, the Turkish version of Academic Motivation Scale was used. After t-tests analysis, it was found out that, statistically there is no significant difference between the motivation types of the state university students and private university students. On the other hand, when compared the motivation types of the female and male students, the paper concluded that there is a significant difference regarding intrinsic, extrinsic and total motivation types in favour of female students.
Keywords: Extrinsic and Intrinsic Motivation; Gender; Medical Education; Type of University; CLASSROOM GOAL STRUCTURE; SELF-EFFICACY; ACHIEVEMENT; PREDICTORS; TEACHERS; SCHOOL; AMOTIVATION; ENGAGEMENT; EDUCATION; Anthropology; Science & Technology - Other Topics; Social Sciences - Other Topics